LO45: Simulation-based research in emergency medicine in Canada: priorities and perspectives. (May 2019) - Chaplin, T.; Thoma, B.; Petrosoniak, A.; Caners, K.; McColl, T.; Forristal, C.; Dakin, C.; Deshaies, J.; Raymond-Dufresne, E.; Fotheringham, M.; Ha, D.; Holm, N.; et al.
Abstract : Introduction : Simulation has assumed an integral role in the Canadian healthcare system with applications in quality improvement, systems development, and medical education. High quality simulation-based research (SBR) is required to ensure the effective and efficient use of this tool. This study sought to establish national SBR priorities and describe the barriers and facilitators of SBR in Emergency Medicine (EM) in Canada.Methods : Simulation leads (SLs) from all fourteen Canadian Departments or Divisions of EM associated with an adult FRCP-EM training program were invited to participate in three surveys and a final consensus meeting. The first survey documented active EM SBR projects. Rounds two and three established and ranked priorities for SBR and identified the perceived barriers and facilitators to SBR at each site. Surveys were completed by SLs at each participating institution, and priority research themes were reviewed by senior faculty for broad input and review.Results : Twenty SLs representing all 14 invited institutions participated in all three rounds of the study. 60 active SBR projects were identified, an average of 4.3 per institution (range 0-17). 49 priorities for SBR in Canada were defined and summarized into seven priority research themes. An additional theme was identified by the senior reviewing faculty. 41 barriers and 34 facilitators of SBR were identified and grouped by theme. Fourteen SLs representing 12 institutions attended the consensus meeting and vetted the final list of eight priority research themes for SBR in Canada: simulation in CBME, simulation for interdisciplinary and inter-professional learning, simulation for summative assessment, simulation for continuing professional development, national curricular development, best practices in simulation-based education, simulation-based education outcomes, and simulation as an investigative methodology.Conclusion : Conclusion: This study has summarized the current SBR activity in EM in Canada, as well as its perceived barriers and facilitators. We also provide a consensus on priority research themes in SBR in EM from the perspective of Canadian simulation leaders. This group of SLs has formed a national simulation-based research group which aims to address these identified priorities with multicenter collaborative studies.